Nurse-led reinforced education by mobile messenger improves the quality of bowel preparation of colonoscopy in a population-based colorectal cancer screening program: a randomized controlled trial - Lam, Thomas Y. T. (2022)
Adequate bowel preparation is an important colonoscopy quality indicator. Reinforced education is effective in improving bowel preparation quality of colonoscopy with mixed indications. However, it remains unclear whether such improvement can be consistently observed in pre- and post-irrigation during colonoscopy in screening population.